ANALISIS TINGKAT PEMAHAMAN GURU EKONOMI DALAM MELAKSANAKAN KEGIATAN PENILAIAN BERDASARKAN KURIKULUM 2013 DI SMA NEGERI SE-KECAMATAN BAGAN SINEMBAH - Mustafa Arifin Arifin; Suarman Suarman; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : The purpose of this study was to determine the economic teachers understanding level to implementing assessment activities based on curriculum 2013 at Public Senior High School in Bagan Sinembah District.The population in this study is the economics teacher at Public Senior High School In Bagan Sinembah District and the sample to be studied was 19 teachers. Data collection using questionnaires. Data analysis uses quantitative descriptive analysis. The results showed the level of understanding of economics teachers in carrying out assessment activities based on the 2013 curriculum that is 38.22%, the level of understanding of economics teachers in carrying out assessment activities based on the 2013 curriculum seen from the assessment plan that is 43.27%, the level of understanding of economics teachers in carrying out assessment activities based on the 2013 curriculum seen from the implementation of the assessment is 31.02%, the level of understanding of the economics teacher in carrying out assessment activities based on the 2013 curriculum viewed from the management of the assessment results is 62.96%, the level of understanding of economics teachers in carrying out assessment activities based on the 2013 curriculum seen from the utilization and follow-up of the assessment results which is 38.89%.Keywords: assessment, understanding level, curriculum 2013.